Circadian abnormalities in a mouse model of high trait anxiety and depression. (May 2014) - Griesauer, Irene; Diao, Weifei; Ronovsky, Marianne; Elbau, Immanuel; Sartori, Simone; Singewald, Nicolas; Pollak, Daniela D.
Abstract: Introduction. Dysregulation of circadian rhythms is a key symptom of mood disorders, including anxiety disorders and depression. Whether the circadian abnormalities observed in depressed patients are cause or consequence of the disease remains elusive. Here we aimed to explore potential disturbances of circadian rhythms in a validated genetic animal model of high trait anxiety and co-morbid depression and examine its molecular correlates. Materials and methods. Mice selectively bred for high (HAB) and normal (NAB) anxiety- and co-segregating depression-like behavior were subjected to analysis of circadian wheel-running activity to determine light-entrained (LD) and free-running circadian (DD) rhythms and a light-induced phase shift. Clock gene expression in HAB/NAB hippocampal tissue was analyzed by qRT-PCR and verified by Western blotting. Results. Compared to NABs, HAB mice were found to present with altered DD length of daily cycle, fragmented ultradiem rhythms, and a blunted phase shift response. Clock gene expression analysis revealed a selective reduction of Cry2 expression in hippocampal tissue of HAB mice. Discussion. We provide first evidence for a dysregulation of circadian rhythms in a mouse model of anxiety and co-morbid depression which suggests an association between depression and altered circadian rhythms at the genetic level and points towards a role for Cry2 .